Rancang Bangun Acwh Berkapasitas 60 Liter Memanfaatkan Pipa Kapiler Bersirip Sebagai Penghantar Panas - Candra A Siregar; A M Siregar; Affandi Affandi; Ulil Amri (Cered Indonesia Institute, 2020)
Air conditioners (AC) and water heaters have become common needs in households and the hotel industry. This shows that the need for electric power is increasing. To reduce electricity consumption which is high enough. Engineering technology needs to be done for air conditioning as well as water heating. This engineering is called ACWH (Air Conditioner Water Heater). The way the ACWH system works is to utilize the wasted heat from the AC system to heat water with the addition of a fin heat exchanger, where the heat exchanger is designed to utilize the energy already in the system. This study used experimental research methods by testing at temperatures of 16, 18 ?, and 20 ? AC. The test results showed that the finned shell helical coil type heat exchanger was able to produce a water temperature of 55 ? in the test with an AC temperature of 18 ?.